Prognostic value of remnant cholesterol in patients with coronary heart disease: A systematic review and meta-analysis of cohort studies - Tian, Yun; Wu, Wenli; Qin, Li; Yu, Xiuqiong; Cai, Lin; Wang, Han; Zhang, Zhen (Frontiers in Cardiovascular Medicine, 2023)
Background: The relationship between abnormal lipid levels and atherosclerotic cardiovascular diseases is well-established, but the association between remnant cholesterol (RC) and coronary heart disease (CHD) remains uncertain. The aim of this meta-analysis is to systematically evaluate the prognostic value of RC concentration in patients with CHD. Methods: PubMed, EMBASE, Cochrane and Web of Science databases were reviewed to identify relevant observational cohort studies published in English up to December 2021. Random effects meta-analysis compared the highest and lowest RC concentration. The primary outcome was a composite of major adverse cardiovascular events (MACEs) and all-cause mortality in CHD patients. Results: Ten studies recruiting 30,605 CHD patients were selected to be included in this meta-analysis. CHD patients with elevated RC concentration had an increased risk of the composite endpoint events (RR=1.54, 95%CI:1.26-1.87) and MACEs (RR=1.70, 95%CI:1.54-1.88), but the risk of all-cause mortality was not statistically significant (RR=1.16, 95%CI: 0.79-1.69, P=0.44). Subgroup analysis showed consistent results. Conclusions: Our results suggest that elevated concentration RC may independently predict MACEs in CHD patients. Determination of RC concentration may improve risk stratification of prognosis in CHD patients. However, more high-quality studies are necessary to confirm this association.